Clinical Investigation of the Efficacy and Safety of Anlotinib with Immunotherapy in Advanced Non-Small Cell Lung Cancer as Third-Line Therapy: A Retrospective Study - Yang, Shengjie (Cancer Manag Res, 2020)
PURPOSE: This study was designed to assess the clinical efficacy and safety of anlotinib with immunotherapy in advanced non-small cell lung cancer as third-line therapy. PATIENTS AND METHODS: A total of 101 patients with advanced non-small cell lung cancer who were treated with anlotinib combined with immunotherapy were evaluated for progression-free survival, objective response rate, and disease control rate. Univariate and multivariate analyses were performed to determine the prognostic factors. The main adverse events were evaluated as per the Common Terminology Criteria for Adverse Events version 5.0. RESULTS: Nineteen patients had partial response (18.8%), 61 had stable disease (60.4%), 31 had progressive disease (20.8%), and no patients achieved complete response (0%). The objective response rate was 18.8%, and the disease control rate was 79.2%. In all patients, the median progression-free survival was 6.7 months (95% confidence interval 6.13–7.24 months). In Cox regression analysis, the Eastern Cooperative Oncology Group performance status score, smoking history and age were predictive indicators for anlotinib treatment efficacy. Treatment-related adverse events were tolerated. CONCLUSION: This study demonstrated and confirmed the clinical effectiveness of anlotinib combined with immunotherapy in advanced non-small cell lung cancer as third-line therapy.